Pyrrolopyrrole-Based Aza-BODIPY Small Molecules for Organic Field-Effect Transistors - Zhang, Daohai; Liang, Dongxu; Gu, Liang; Zhang, Haichang (Frontiers in Chemistry, 2022)
Due to the good planarity, π-conjugate structure, thermal stability and structural modifiability of DPP structure, the performances of diketopyrrolopyrrole (DPP) in the field of optoelectronics, such as organic solar cells (OSC), organic photovoltaic (OPV), organic field effect transistors (OFET) etc., have been attracted more and more attention by the scientific society. Herein, a new small molecule pyrrolopyrrole aza-BODIPY (PPAB) based on thiophene substituted DPP structure was developed by using the Schiff-base formation reaction of diketopyrrolopyrrole and heteroaromatic amines. Absorption spectroscopy, electrochemistry, X-ray diffraction, molecular theoretical simulation calculation and the organic filed-effect transistor properties based on the PPAB were investigate. It was found that PPAB exhibits a broad absorption in the visible (Vis) and near infrared (NIR) region, which is contributed to its long-range conjugate structure. In addition, it is worth noting that PPAB has multiple F atoms leading to the low LUMO level, which is conducive to the injection and transportation of charge carriers between the semiconductor layer and the electrode. Meanwhile, its hole carrier mobility is up to 1.3×10-3 cm2 V-1 s-1 due to its large conjugate structure, good intramolecular charge transfer (ICT) effect and high degree of coplanarity. This work provides a new chromophore with electron-deficient ability for the design high-performance semiconductors.